Green technology - Hobbs, Mike, 1954- (Mankato, Minnesota : Smart Apple Media, 2014)
"Students interested in eco-technology learn what it takes to become young entrepreneurs in the industry. Successful inventors of environmental and "green" gadgets and products are spotlighted, and instructions are given to jumpstart ideas and business plans. Questions throughout the book challenge critical thinking"--
What is green technology? -- What makes a successful ecopreneur? -- Green brainstorming -- Researching your market -- Finding start-up funds -- Developing your product -- Making the most of being green -- Know your competition -- Financial planning -- Building your team -- Learn to be decisive -- Work out a marketing plan -- Making your story heard -- Launch time -- Boosting sales and distribution -- Turning problems into gains -- So what's next?.
Grade 7 to 8.
Includes bibliographical references and index.
1 2
Keywords: Green products -- Juvenile literature; Green technology -- Juvenile literature; Entrepreneurship -- Juvenile literature; Green movement -- Economic aspects -- Juvenile literature; New business enterprises -- Juvenile literature